2023
DOI: 10.1002/ange.202304515
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Photophysical Properties with Stereochemical Expression of 6s2 Lone Pairs in Two‐dimensional Lead Halide Perovskites

Abstract: Two‐dimensional (2D) lead halide perovskites (LHPs) have shown great promises for light‐emitting applications and excitonic devices. Fulfilling these promises demands an in‐depth understanding on the relationships between the structural dynamics and exciton‐phonon interactions that govern the optical properties. Here, we unveil the structural dynamics of 2D lead iodide perovskites with different spacer cations. Loose packing of an undersized spacer cation leads to out‐of‐plane octahedral tilting, whereas compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The control film in Figure 5f showed some nonluminescent grain boundaries, indicating that there were nonradiative recombination centers in these areas. 38,39 Highly tensile films with a low additive concentration showed reduced luminescence at both the boundaries and the bulk of the film (Figure 5g), which could be attributed to an increase in nonradiative recombination across the film. However, for a compressive sample, the grain boundaries were luminescing at a higher intensity (Figure 5h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The control film in Figure 5f showed some nonluminescent grain boundaries, indicating that there were nonradiative recombination centers in these areas. 38,39 Highly tensile films with a low additive concentration showed reduced luminescence at both the boundaries and the bulk of the film (Figure 5g), which could be attributed to an increase in nonradiative recombination across the film. However, for a compressive sample, the grain boundaries were luminescing at a higher intensity (Figure 5h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Huang et al reported that lone-pair activity can be enhanced via increasing the size of the A-site cation of halide perovskites, which promotes Pb off-center displacement. This is specially manifested in two-dimensional (2D) halide perovskites that can accommodate a relatively larger size cation in comparison with their three-dimensional (3D) counterparts, leading to a stronger stereochemical character of LPEs and more possibility to obtain ferroelectricity or antiferroelectricity in 2D halide perovskites. , Although this progress has been made in promoting the stereochemical character of LPEs, there is still a lack of thorough understanding about to what extent the stereochemical activity of LPEs can be enhanced to induce and modulate the physical properties of materials containing LPEs, such as FE properties. Here, by taking bismuth oxychalcogenides Bi 2 O 2 X (X = S, Se and Te) as model systems, we engineer the activity of LPEs systematically to induce the phase transition and ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%